$f(x) = (x + log x) (x – 1)$

$f(x) = (x + \log x) (x – 1)$
$f'(x) = (1 + 1/x) (x – 1) + (x + \log x) \cdot 1 =$ $\frac{(x + 1)}{x}\cdot (x – 1) + (x + \log x) =$ $\frac{x^2 – 1}{x} + (x + \log x) =$ $\frac{x^2 – 1 + x^2 + x\log x}{x} = 2x + \log x -\frac{1}{x}$

Commenti

commenti

C'è un commento su questo articolo:

  1. Della funzione
    y=(x-logx)(x-1),
    y’=2x+logx-log.e/x+log.e-1.
    Dimostrazione.
    y’=(x+log.x)D(x-1)+
    +(x-1)D(x+log.x)=
    (x+log.x)+(x-1)(1+log.e/x)=
    =x+log.x+x+log.e-1-log.e/x=
    =2x+log.x+log.e-log.e/x-1,
    derivata della funzione.
    Nel punto P(xP=2,yP=2,3010196)
    della funzione,y’=3,5181775 ;
    y’=3,5181772x-4,735325004,
    equazione della tangente in P.
    y’=2x+log.x-1/x è errata.